Convergence of cortical and thalamic input to direct and indirect pathway medium spiny neurons in the striatum. - Huerta-Ocampo, I; Mena-Segovia, J; Bolam, J (2014)
The major afferent innervation of the basal ganglia is derived from the cortex and the thalamus. These excitatory inputs mainly target the striatum where they innervate the principal type of striatal neuron, the medium-sized spiny neurons (MSNs), and are critical in the expression of basal ganglia function. The aim of this work was to test directly whether corticostriatal and thalamostriatal terminals make convergent synaptic contact with individual direct and indirect pathway MSNs. Individual MSNs were recorded in vivo and labelled by the juxtacellular method in the striatum of BAC transgenic mice in which green fluorescent protein reports the expression of dopamine D1 or D2 receptors. After recovery of the neurons, the tissue was immunolabelled for vesicular glutamate transporters type 1 and 2, as markers of cortical and thalamic terminals, respectively. Three of each class of MSNs were reconstructed in 3D and second-order dendrites selected for electron microscopic analysis. Our findings show that direct and indirect pathway MSNs, located in the matrix compartment of the striatum, receive convergent input from cortex and thalamus preferentially on their spines. There were no differences in the pattern of innervation of direct and indirect pathway MSNs, but the cortical input is more prominent in both and synaptic density is greater for direct pathway neurons. The 3D reconstructions revealed no morphological differences between direct and indirect MSNs. Overall, our findings demonstrate that direct and indirect pathway MSNs located in the matrix receive convergent cortical and thalamic input and suggest that both cortical and thalamic inputs are involved in the activation of MSNs.